Strategic Integration of Creative and Blue Economies through Digital Media: A Case Study of PT Digipedia Karya Pratama in Indonesia’s Maritime Region - Yudistia, Tasya Takhayaza; Hasrullah, Hasrullah; Yahya, Muhammad; Rahmadiansyah, Afique (Universitas Ahmad Dahlan, 2025)
This study explores the strategic integration of creative industry practices and blue economy principles through the lens of a small digital media enterprise in Indonesia’s Riau Islands. Using a qualitative case study approach, it investigates how PT Digipedia Karya Pratama navigates structural constraints—such as limited human capital, financing, and innovation capacity—to engage in sustainable digital innovation. Data were collected through semi-structured interviews, document analysis, and direct observation, and analyzed thematically alongside a SWOT framework. Findings reveal that while the company’s strengths lie in institutional networks and cultural embeddedness, it struggles with underdeveloped game development initiatives and insufficient engagement in regional innovation ecosystems. However, its strategic location and narrative capital offer pathways for leveraging marine sustainability themes through serious games and digital storytelling. The study contributes to the literature by highlighting the role of peripheral creative firms in aligning digital transformation with blue economy goals, proposing a replicable model for innovation-driven development in coastal regions. Practical recommendations are offered to strengthen talent development, multi-stakeholder collaboration, and culturally grounded game production. This case contributes to the discourse on inclusive innovation, sustainability communication, and creative economy policy in emerging economies.